Features of forming the professional competency of would be teachers during extracurricular activity - V. Ketrish, Evgeniya; V. Andryukhina, Tatiana; V. TretyakovÐ°, Natalya; E. Safronovich, Irina; A. Papshev, Ivan (International Journal of Engineering and Technology, 2018)
The topicality of the issue under study is due to the need to research the features of forming the professional competency of would-be teachers during extracurricular activity and independent learning of students, under the condition of introducing a competency approach into the modern educational system (by the example of would-be Physical Training teachers). The article objective is to disclose the conditions of forming the professional competence of a would-be Physical Training teacher, and to elaborate a complex of extracurricular pedagogical measures which would promote the more effective forming the professional competence. The leading approach to the research of the stated problem is the competency-activity approach, serving as the practice-oriented tactics of research and showing that the main direct result of educational activity, as for our research, is forming a set of professional competencies underlying the professional competency of a teacher. The research results are presented, which show that the most important role in the structure of professional competency of a Physical Training teacher, providing his/her successful professional functioning, is played by subject-professional, communicative and analytical-reflective component, as well as certain individual-personal qualities of a would-be teacher. The unity and integrity of these components are the dominants of a Physical Training teacher performance; hence, they are the obligatory elements of his/her professional training within the process of both curricular and extracurricular activity and independent learning. The materials of the research will be useful for the scholars studying the issues of introducing a competency approach into the Russian educational system, for the specialists engaged in organization of studies in the higher and secondary professional educational establishments, for pedagogues working at various educational establishments, for students of pedagogical universities and other persons concerned.Â Â